The lncRNA NEAT1 promotes the epithelial-mesenchymal transition and metastasis of osteosarcoma cells by sponging miR-483 to upregulate STAT3 expression - Yan Chen; Jun Li; Jia-Kun Xiao; Lei Xiao; Bin-Wu Xu; Chen Li (Cancer Cell International, 2021)
Abstract Background Osteosarcoma is one of the most prevalent primary bone tumours in adolescents. Accumulating evidence shows that aberrant expression of the long non-coding RNA (lncRNA) NEAT1 and microRNA-483 (miR-483) contribute to the epithelial-mesenchymal transition (EMT), invasion and metastasis of tumour cells. However, the potential regulatory effects of NEAT1 and miR-483 on the EMT of osteosarcoma remain elusive. Methods The expression of the NEAT1, miR-483, signal transducer and activator of transcription-1 (STAT1), STAT3, and EMT-associated markers was measured using qRT-PCR or western blotting. NEAT1 overexpression or knockdown was induced by lentivirus-mediated transfection. A luciferase reporter assay was employed to confirm the association between NEAT1/miR-483 and miR-483/STAT3. RNA immunoprecipitation (RIP) was also performed to verify the NEAT1 and miR-483 interaction. Wound healing and transwell assays were implemented to assess the migration and invasion of U2OS cells. Unilateral subcutaneous injection of U2OS into nude mice was performed to investigate tumour metastasis in vivo. Results The expression of miR-483 was downregulated in both osteosarcoma cell lines and osteosarcoma tissues. The overexpression of miR-483 suppressed the migration, invasion, and expression of EMT-associated proteins in U2OS cells, while simultaneous overexpression of STAT3 partially relieved this suppression. Mechanistically, miR-483 specifically targeted the 3′ untranslated region (3′UTR) of STAT3 and repressed its expression. However, NEAT1 sponged miR-438, increased STAT3 expression, and repressed STAT1 expression, subsequently increasing the EMT of osteosarcoma cells. The knockdown of NEAT1 in transplanted U2OS cells impaired the liver and lung metastases of osteosarcoma in nude mice. Moreover, NEAT1 silencing inhibited the mesenchymal- epithelial transition (MET) of osteosarcoma at metastasis sites. Conclusions The lncRNA NEAT1/miR-483/STAT3 axis plays a crucial role in regulating the metastasis of osteosarcoma and potentially represents one appealing therapeutic target for osteosarcoma treatment in the future.